The psychology of language from data to theory - Harley, Trevor A. (London Psychology Press, 2014)
"Now in full colour, this fully revised edition of the best-selling textbook provides an up-to-date and comprehensive introduction to the psychology of language for undergraduates, postgraduates, and researchers. It contains everything the student needs to know about how we acquire, understand, produce, and store language. Whilst maintaining both the structure of the previous editions and the emphasis on cognitive processing, this fourth edition has been thoroughly updated to include: the latest research, including recent results from the fast-moving field of brain imaging and studies updated coverage of key ideas and models an expanded glossary more real-life examples and illustrations. The Psychology of Language, Fourth Edition is praised for describing complex ideas in a clear and approachable style, and assumes no prior knowledge other than a grounding in the basic concepts of cognitive psychology. It will be essential reading for advanced undergraduate and graduate students of cognition, psycholinguistics or the psychology of language. It will also be useful for those on speech and language therapy courses. The book is supported by a companion website featuring a range of helpful supplementary resources for both students and lecturers"-- Provided by publisher.
"This fully revised edition of the popular textbook provides an up-to-date and comprehensive introduction to the psychology of language for undergraduates, postgraduates, and researchers. It contains everything the student needs to know about how we acquire, understand, produce, and store language. The Psychology of Language, 4th Edition, covers all the main topics in the psychology of language, such as language production, comprehension, syntax and parsing, reading development, and word recognition. In addition, this text covers language acquisition, how language is related to thought, bilingualism and second language acquisition. Following a strong developmental theme, it also describes how children acquire language while demonstrating how this is related to the brain and to other aspects of cognition. Whilst maintaining both the structure of the previous editions and the emphasis on cognitive processing, this fourth edition has been thoroughly updated with all the latest and cutting-edge research. In particular, the book takes into account recent research into cognitive neuroscience and the relationship between language and the brain. The Psychology of Language, 4th Edition describes complex ideas in a clear and approachable style, and assumes no prior knowledge other than a grounding in the basic concepts of cognitive psychology. It will be essential reading for advanced undergraduate and graduate students of cognition, psycholinguistics or the psychology of language. It will also be useful for those on speech and language therapy courses. The Psychology of Language, 4th Edition, is supported by a companion website featuring a range of helpful supplementary resources for both students and lecturers"-- Provided by publisher.
Section A. Introduction : The study of language : Why study language and why is it so difficult ; What is language? ; How has language changed over time? ; What is language for? ; The history and methods of psycholinguistics ; Models in psycholinguistics ; Language and the brain ; Themes and controversies -- Describing language : How to describe speech sounds ; Consonants ; Vowels ; Syllables ; Linguistic approaches to syntax -- Section B. The biological and developmental bases of language : The foundation of language : Where did language come from? ; Do animals have language? ; The biological basis of language ; Is there a critical period for language development? ; The cognitive basis of language ; The social basis of language ; The language development of visually and hearing-impaired children ; What is the relation between language and thought? -- Language development : What drives language development? ; The language acquisition device ; How children develop language ; Phonological development ; Lexical and semantic development ; Syntactic development -- Bilingualism and second language acquisition : Bilingualism ; Second language acquisition ; Evaluation of work on bilingualism and second language acquisition -- Section C. Word recognition : Recognizing visual words : Basic methods and findings ; What makes word recognition easier (or harder)? ; Attentional processes in visual word recognition ; Do different tasks give consistent results? ; Is there a dedicated visual word recognition system? ; Meaning-based facilitation of visual word recognition ; Processing morphologically complex words ; Models of visual word recognition ; Coping with lexical ambiguity -- Reading : The writing system : A preliminary model of reading ; The processes of normal reading ; The neuroscience of adult reading disorders ; Models of word naming ; Connectionist models of dyslexia ; Comparison of models -- Learning to read and spell : Normal reading development ; Phonological awareness ; How should reading be taught? ; Learning to spell ; Developmental dyslexia -- Understanding speech : Recognizing speech ; Models of speech recognition ; The neuroscience of spoken word recognition -- Section D. Meaning and using language : Understanding the structure of sentences ; Dealing with structural ambiguity ; Early work in parsing ; Processing structural ambiguity ; Gaps, traces, and unbounded dependencies ; The neuroscience of parsing -- Word meaning : Classic approaches to semantics ; Semantic networks ; Semantic features ; Family resemblance models ; Combining concepts ; Figurative language ; The neuroscience of semantics ; Connectionist approaches to semantics -- Comprehension : Memory of text and inferences ; Reference and ambiguity ; Models of text processing ; Individual differences in comprehension skills ; The neuroscience of text processing -- Section E. Production and other aspects of language : Language production : Slips of the tongue ; Syntactic planning ; Lexicalization ; Phonological encoding ; The analysis of hesitations ; The neuroscience of speech productions ; Writing and agraphia -- How do we use language? : Making inferences in conversation ; The structure of conversation ; Collaboration in dialog -- The structure of language system : What are the modules of language? ; How many lexicons are there? ; Language and short-term memory -- New directions : Themes in psycholinguistics revisited ; Some growth areas? -- Appendix : Connectionism : Interactive activation models ; Back-propagation -- Glossary : Example of sentence analysis.
Dr. Flora Generalao (Recommending faculty) : BA Psychology Program
Includes bibliographical references (pages 495-568)
Includes bibliographical references (p. 495-568) and index.
Keywords: Psycholinguistics; Psycholinguistics; Language Development; Leermiddelen (vorm)